The Regulation Mechanism of Electricity Market on Load Side Resources Based on the Economic Person Hypothesis - Zhiyuan GAO; Weijin ZHUANG; Jian GENG; Feng LI; Bike XUE; Xiaolei YANG; Keju BAI (Zhongguo dianli)
In order to make full use of the load-side regulation capacity, it is necessary to conduct an in-depth research on the regulation mechanism of the market-oriented mechanism on the load side. Based on the different regulatory purposes and signal sources for different types of loads in the market, the market-oriented regulatory role is generally divided into two categories: electricity price regulation and interactive regulation. Based on the assumption of economic man in classical economics, the mechanisms of electricity price regulation and interactive regulation for different types of loads are studied in terms of cost, benefits, and other factors. Furthermore, the differences and connections between electricity price regulation and interactive regulation are qualitatively analyzed and quantitatively compared. Case study results show that the electricity price regulation always works as ordinary market through pursuit of surplus maximization on the load side, and the interactive regulation is a kind of market-oriented tool that market operators use on demand to pursue social welfare maximization, and the action mechanism of the two is quite different, but also interrelated.